Coin Circulation in the Vyatka Region in the 30-90s of the 18th Century (according to the Data of Coin Treasures) - E. Y. Mokerova; K. N. Tarasov (Научный диалог, 2020)
The article is devoted to the issues of coin circulation in the Vyatka region (province) in the 30-90s of the 18th century. On the basis of a topographic summary compiled by the authors, the findings of coin treasure complexes are characterized. It is noted that, unlike previous periods, the treasures of coins of the XVIII century are divided into categories of coin metals. When analyzing coin complexes, the conclusion is made: in the territory of the Vyatka region, copper coins took the place of a silver penny and began to dominate money circulation from the second half of the 18th century, although a copper coin appeared as legal tender in Peter's time. The circulation of copper coins is determined, which make up the majority of the treasures of finds of the indicated period, mainly in the circle of the social lower classes of society. It is emphasized that the large copper treasures, large in size and weight, do not indicate an increase in the standard of living of the population, but are a reaction of the population to the depreciation of bank notes. The reasons for the population’s motivation for hoarding coin complexes are explored: an active foreign policy, the growth of industry and trade, monetary crises and related reforms and innovations, and tax increase.